Structural Instability of Metallic Islands on Liquid Substrates - Ajeeb, Saida; Lv, Neng; Zhang, Chuhang; Pan, Qifa; Xia, Agen; Ye, Gaoxiang (Current Nanoscience, 2014)
We study the structural instability of gold (Au) and silver (Ag) islands with the size of the order of 103nm on silicone oil surfaces at room temperature. The samples are prepared by the thermal evaporation method. For the Ag system, after the sample is removed from the vacuum chamber, the apparent island coverage of the total area decreases obviously (≥8.0%). As the topological structure of the islands evolves, the decay of the total area of each island may be more than 12%. The microstructure of the Au islands, however, is relatively stable. The interpretation for the experimental results is presented.
Keywords: structural instability